The Influence of Leadership and Skills on Improving Employee Performance with Job Satisfaction as a Moderating Variable in Brown Sugar MSMEs in Pegajahan Village, Serdang Bedagai - Rukmini Rukmini; Muhammad Rizaldy Wibowo; Nova Azahra; Sri Murniyanti; Nur'Ain Harahap; Nicky Astria Hutapea (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
This study aims to test and analyze the influence of Leadership and Skills on Employee Performance with an understanding of Employee Job Satisfaction as a moderating variable in Brown Sugar MSMEs in Pegajahan Village, Deli Serdang. The urgency of this research is expected to provide benefits to the general public in terms of HR management in the business world, and especially the owners and employees of Brown Sugar MSMEs in Pegajahan Village, Deli Serdang. Where MSMEs are one of the means of improving the people's economic welfare and alleviating poverty. To be able to perform optimally, leadership knowledge and qualified skills are needed. To be able to improve company performance, it is necessary to pay attention to employee job satisfaction. This study uses an associative approach. The population in this study is all brown sugar MSMEs in Pegajahan Village, totaling 100 people. The sample used is a saturated sample of 100 people in Pegajahan Village MSMEs. Data collection uses observation and questionnaires. Data analysis uses a quantitative descriptive approach, using statistical analysis using the Author Model analysis test, Inner Model and Hypothesis Testing. Data processing using PLS (Partial Least Square) software. This study shows that Leadership and Work Skills have a significant effect on employee performance. Satisfaction is able to mediate the influence of Leadership and Work Skills on Employee Performance in Brown Sugar MSMEs in Pegajahan Village, Deli Serdang Regency. Leadership, Skills and Job Satisfaction affect Employee Performance with an R-Square value of 0.718. The variability of the Performance construct can be explained by the variability of the Leadership, Skills and Job Satisfaction constructs of 71.80%.